Applicability of vancomycin, meropenem, and linezolid in capillary microsamples vs. dried blood spots: A pilot study for microsampling in critically ill children - Xiaoyong, Xu; Jinglin, Wang; Guangfei, Wang; Huimin, Zhang; Hong, Xu; Zhiping, Li (Frontiers in Pediatrics, 2023)
Therapeutic drug monitoring (TDM) has been shown to be clinically beneficial for critically ill patients. However, this is a burden for neonates or children with small circulating blood volumes. Here, we aimed to develop and validate a microsampling TDM platform (including dried blood spots (DBS) and capillary microsamples (CMS)) for the simultaneous quantification of vancomycin, meropenem, and linezolid. Paired DBS and CMS samples were obtained from an intensive care unit (ICU) to evaluate its clinical application. Estimated plasma concentrations (EPC) were calculated from DBS concentrations. Agreement between methods was evaluated using Deming regression and Bland–Altman difference plots. Results for the microsampling methods validation showed excellent reliability and compatibility with the analysis of the sample matrix and hematocrit range of the studied population. The DBS and CMS accuracy and precision results were within accepted ranges and samples were stable at room temperature for at least 2 days and 8 h, respectively. Hematocrit had no impact on CMS, but sightly impacted DBS measurements. The CMS and DBS antibiotic concentrations correlated well (r > 0.98). The drug concentration ratio in DBS samples to that in CMS was 1.39 for vancomycin, 1.34 for meropenem, and 0.94 for linezolid. The EPC calculated from the DBS using individual hematocrit ranges presented comparable absolute values for vancomycin (slope: 1.06) and meropenem (slope: 1.04), with a mean of 98 % and 99 % of the measured CMS concentrations, respectively. This study provides a microsampling TDM platform validated for clinical use for a rapid quantification of three antibiotics and is suitable for real-time TDM-guided personalization of antimicrobial treatment in critically ill children.